The active constituent of pine needle oil, bornyl acetate, suppresses NSCLC progression by inhibiting the PI3K/AKT/ABCB1 signaling axis - Wu, Jieheng; Ren, Jiaming; Wang, Lu; Yang, Zeyang; Wang, Xuanyin; Tu, Ziyi; Liu, Xinlei; Wang, Ye; Cao, Yaxuan; Zhu, Xu; Li, Long; Lu, Maoqin; et al. (Frontiers in Pharmacology, 2025)
IntroductionNon-small cell lung cancer (NSCLC) is a leading cause of cancer-related mortality worldwide. Although targeted therapies and immunotherapies have improved treatment outcomes, the development of drug resistance continues to limit clinical efficacy. This study aims to explore the potential therapeutic effects and molecular mechanisms of pine needle oil and its key bioactive component, bornyl acetate (BA), in NSCLC.MethodsThe anti-cancer activity of BA was evaluated in vitro using two NSCLC cell lines, A549 and NCI-H460. Cell proliferation, invasion, migration, colony formation, and apoptosis were assessed. Mechanistic studies focused on the PI3K/AKT signaling pathway and ABCB1 expression levels. The AKT agonist SC79 was used to rescue phenotypic effects. In vivo, subcutaneous xenograft models generated with NCI-H460 and A549 cells were employed to examine the antitumor efficacy of BA.ResultsBA significantly inhibited proliferation, invasion, migration, and colony formation in A549 and NCI-H460 cells and promoted apoptosis. Mechanistically, BA suppressed the PI3K/AKT pathway, leading to downregulation of ABCB1. The AKT activator SC79 partially reversed BA-induced inhibition of invasion and migration. In vivo, BA treatment markedly attenuated the growth of both A549 and NCI-H460 xenograft tumors.DiscussionThese results demonstrate that BA exerts potent anti-tumor effects in NSCLC by inhibiting the PI3K/AKT/ABCB1 axis. The findings provide a mechanistic rationale for the development of BA and other natural product-based therapies, particularly for the treatment of drug-resistant NSCLC.